Effective Small Interfering RNA Therapy to Treat CLCN7-dependent Autosomal Dominant Osteopetrosis Type 2 - Mattia Capulli; Antonio Maurizi; Luca Ventura; Nadia Rucci; Anna Teti (Elsevier, 2015)
In about 70% of patients affected by autosomal dominant osteopetrosis type 2 (ADO2), osteoclast activity is reduced by heterozygous mutations of the CLCN7 gene, encoding the ClC-7 chloride/hydrogen antiporter. CLCN7G215R-, CLCN7R767W-, and CLCN7R286W-specific siRNAs silenced transfected mutant mRNA/EGFP in HEK293 cells, in RAW264.7 cells and in human osteoclasts, with no change of CLCN7WT mRNA and no effect of scrambled siRNA on the mutant transcripts. Osteoclasts from Clcn7G213R ADO2 mice showed reduced bone resorption, a condition rescued by Clcn7G213R-specific siRNA. Treatment of ADO2 mice with Clcn7G213R-specific siRNA induced increase of bone resorption variables and decrease of trabecular bone mass, leading to an overall improvement of the osteopetrotic bone phenotype. Treatment did not induce overt adverse effects and was effective also with siRNAs specific for other mutants. These results demonstrate that a siRNA-based experimental treatment of ADO2 is feasible, and underscore a translational impact for future strategy to cure this therapeutically neglected form of osteopetrosis.